Defending the Next Frontier: Artificial Intelligence and the Future of Cybersecurity Warfare (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The field of cybersecurity is constantly changing and evolving. Recently, artificial intelligence (AI) has emerged as a game-changer which has the potential to revolutionize both defensive and offensive cyber operations. Although AI can improve cybersecurity capabilities, it also presents new challenges and risks that need to be carefully evaluated and addressed. This paper explores the many aspects of AI in cybersecurity warfare, analyzing its advantages, limitations, and ethicalimplications.